Roget's thesaurus of English words and phrases - Davidson, George W. (Penguin, 2002)
Roget's Thesaurus ranks as one of the greatest English language reference works, used for generations by anyone looking for help in order to write a letter, prepare a speech, solve a crossword, or write any manner of prose or poem. Its sales now exceed 32 million copies. This concise edition contains the essential entries from the original 1852 volume, and has been revised and updated to include all the latest buzzwords and phrases.